Analysis of the capital cost impact on share value - Galinienė, Birutė; Butvilas, Andrius (Technological and Economic Development of Economy, 2010)
One of the most important business management tasks for enterprises is the calculation of an appropriate rate of return for invested capital or cost of capital. The article presents a theoretical and practical analysis of four of the most commonly used capital cost evaluation models. Based on the results, the two most suitable capital cost evaluation models that can be used under the prevailing conditions in Lithuania are identified. The analysis of the influence of the cost of capital on share values revealed the factual influence of the valuation models on share values. Thus, based on the research results, the authors recommend that under the current conditions, the Capital Asset Pricing Model and the Fama‐French model can be applied in the share valuation process.Article in English.Kapitalo sąnaudų įtakos akcijų vertei analizėSantrauka. Vienas svarbiausių įmonės verslo vertinimo uždavinių ‐ tinkamas rizikos ir investuoto kapitalo gražos įvertinimas. Straipsnyje pateikiama keturių dažniausiai praktikoje taikomų kapitalo sąnaudų vertinimo modelių teorinė ir praktinė analizė. Remiantis gautais rezultatais išskiriami du tinkamiausi modeliai kapitalo sąnaudoms vertinti Lietuvos sąlygomis. Atlikta kapitalo sanaudų įtakos akcijų vertei analizė parodė faktinę vertinimo metodo įtaka prognozuojamai akcijų vertei. Remdamiesi tyrimo rezultatais autoriai siūlo šiuo metu akcijų vertinimo procese taikyti kapitalo aktyvų vertinimo modelį bei Fama ir French modelį.Reikšminiai žodžiai: verslo vertinimas, verslo vertė, vidutinės svertinės kapitalo sąnaudos, kapitalo sanaudų vertinimo modelis, kapitalo sąnaudos, verslo vertė veikiantys veiksniai, jautrumo analizė.First pyblished online: 21 Oct 2010